2015
DOI: 10.4103/2008-7802.162952
|View full text |Cite
|
Sign up to set email alerts
|

Spatial analysis of Neonatal Congenital Hypothyroidism and Nitrate as an environmental pollutant in Isfahan Province during 2010-2013

Abstract: Background:Thyroid absorption of iodine could be encumbered by nitrate drinking water when it is transported to the fetal thyroid gland. Therefore, nitrate potentially causes congenital hypothyroidism (CH) due to thyroid dysfunction. In this study, we have not only aimed at spatial determination of CH distribution and nitrate concentration (NC) existing in drinking water, but also we intended to evaluate the probable impact of nitrate on CH incidence.Methods:Annual average of nitrate in drinking-water as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…They concluded that ClO 2 was a risk factor for CH in preterm and low-birth-weight neonates (26). In another study in Iran, Mehrnejat et al found no significant relationship between nitrate concentration in drinking water and the incidence of CH through linear regression analysis (58).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…They concluded that ClO 2 was a risk factor for CH in preterm and low-birth-weight neonates (26). In another study in Iran, Mehrnejat et al found no significant relationship between nitrate concentration in drinking water and the incidence of CH through linear regression analysis (58).…”
Section: Discussionmentioning
confidence: 97%
“…Some of the reported risk factors, including environmental pollutants (25,58), dietary component of mothers during prenatal period (41,64), neonatal jaundice (47), maternal anemia (48), intrauterine growth retardation (6), lower weight gain during pregnancy (60), urbanization (62), parental occupation and education (35,47), gestational diabetes (6,46,59), and smoking (14,47,60) have limited evidence. It seems that more studies for investigating the association of the mentioned risk factors with CH are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…According to the results, there was no significant relationship between nitrate concentration in water and CH incidence. [ 25 ]…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, persistence or residual goiters have also been observed in post-salt iodization phase in a community with a goitrogen [43], indicating the effect of goitrogens in adequate iodine prophylaxis. In addition, authors reveal that moderate intake of iodine, adequate to meet iodine requirement, may not ensure normal functioning of thyroid in the presence of goitrogens [44], a situation that is obvious during the consumption of contaminated kaolin.…”
Section: Ingredientsmentioning
confidence: 98%